The shock compression of microorganism-loaded broths and emulsions: experiments and simulations - Hazell, Paul J.; Beveridge, C.; Groves, Kathy H. M.; Appleby-Thomas, Gareth J. (Elsevier, 2010)
By carefully selecting flyer plate thickness and the geometry of a target capsule for bacterial broths and emulsions, we have successfully subjected the contents of the capsule to simultaneous shock and dynamic compression when subjected to a flyer-plate impact experiment. The capsules were designed to be recovered intact so that post experimental analysis could be done on the contents. ANSYS® AUTODYN hydrocode simulations were carried out to interrogate the deformation of the cover plate and the wave propagation in the fluid. Accordingly, we have shown that microorganisms such as Escherichia coli, Enterococcus faecalis and Zygosaccharomyces bailii are not affected by this type of loading regime. However, by introducing a cavity behind the broth we were able to observe limited kill in the yeast sample. Further, on using this latter technique with emulsions it was shown that greater emulsification of an oil-based emulsion occurred due to the cavitation that was introduced.
Keywords: Shock wave; Capsule design; Bacteria; Yeast; Emulsification